Case study on queues : models analysis of service centre - Yong, Wei Der. (2009)
Queue situation is a common problem in our daily life. A service center also treated as a queueing system. In this report, the author will discuss and analysis the Woodlands branch office of Housing Development Board (HDB). First, the author will introduce the queue system and the reason of choosing this service center. The objective of this project is minimizing buffer size to lower customer loss probability. The system is M/Ek/s/k model which decided by its coefficient of variation. The optimal buffer size of M/Ek/s/k model will carry out by the approximation of M/M/s/k and M/D/s/k. The project wills analysis the queue system to reach the preset requirement. The optimal solution will minimize the loss probability of system to one percent with optimal system buffer size which around 11. For additional consideration, the waiting time in queue, total expected revenue and operation cost also would be briefly discussed in the report. Suggestion for reducing delays also would be presented in later part of the report. The author will mention the problems and limitations which reduce the accuracy of the results. Finally, conclusion will conclude the result and research finding of project. Future work for the same kind of system should consider Markov Modulated Poisson Process for customer arrival distribution.